THEORETICAL-STUDIES OF THE FULLERENES - C34 TO C70 - Manolopoulos, D; May, J; Down, S (1991)
An interesting correlation is found between the kinetic stabilities of the fullerenes C34 to C70, as determined by simple Hückel theory HOMO-LUMO energy separations, and the intensities of photoionisation signals from carbon clusters produced by laser vaporisation of graphite. This correlation provides further circumstantial evidence that the observed C34 to C70 clusters are indeed fullerenes, closed carbon cages containing only five- and six-membered rings. © 1991.